2020
DOI: 10.21203/rs.3.rs-55725/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the direct quantitation of SARS-CoV-2 by droplet digital PCR

Abstract: Droplet digital PCR (ddPCR) is a sensitive and reproducible technology widely used for quantitation of several different viruses. The aim of this study was to compare the 2019-nCoV CDC ddPCR Triplex Probe Assay (BioRad) performance on the direct quantitation of SARS-CoV-2 on nasopharyngeal swab respect to the procedure applied to the extracted RNA. Moreover, the two widely used swab types were compared (UTM 3mL and ESwab 1mL, COPAN). A total of 50 nasopharyngeal swabs (n=25 UTM 3mL and n=25 ESwab 1mL) from SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Using ddPCR, it has been shown that SARS-CoV-2 could reliably be detected from nasopharyngeal samples without RNA extraction [18,19]. In our flowchart (Figure 8A), we also highlight this as a possibility even though we did not explore it.…”
Section: Discussionmentioning
confidence: 85%
“…Using ddPCR, it has been shown that SARS-CoV-2 could reliably be detected from nasopharyngeal samples without RNA extraction [18,19]. In our flowchart (Figure 8A), we also highlight this as a possibility even though we did not explore it.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, Equations ( 1) and ( 2) can be modified as Equation (5). Magnetic permeability is a property of a substance that can be denoted by 𝜇 = 𝜇 0 (1 + 𝜒), in which 𝜒 is the magnetic susceptibility.…”
Section: Governing Equations and Numerical Discretization Methodsmentioning
confidence: 99%
“…The dynamics of droplet formation has been investigated numerically, experimentally, and theoretically in different geometries including nozzles [1], and lab-on-a-chip systems [2]. Droplet generation has been utilized in various applications, such as 3D printing [3], electrosprays [4], and bioengineering [5]. Droplet formation is performed by passive or active methods, which differ in the absence or presence of an external force.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of droplet formation has been investigated numerically, experimentally, and theoretically in different geometries, including nozzles 1 and lab-on-a-chip systems 2 . Droplet generation has been utilized in various applications, such as 3D printing 3 , electrosprays 4 , and bioengineering 5 . Droplet formation is performed by passive 6 or active 7 methods, which differ in the absence or presence of an external force.…”
Section: Introductionmentioning
confidence: 99%